1981
DOI: 10.1029/jb086ib03p01776
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stress on radon emanation from rock

Abstract: A uranium‐bearing granitic rock of known radon emanation was deformed to failure under uniaxial stress. Radon emanation and microcrack activity were recorded continuously during the test. Radon concentration in the closed system was measured by an alpha detector. A decrease in emanation was observed during the initial loading of the sample and is interpreted as associated with the closure of pre‐existing cracks within the rock. At a uniaxial stress equal to approximately one‐half the ultimate strength, a tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 10 publications
(7 reference statements)
2
52
0
Order By: Relevance
“…Dissolution or alteration of fresh rock surfaces could significantly increase ion concentrations present in groundwater and would be especially noticeable in well-established aquifers where older rock surfaces have been passivated by the formation of equilibrium alteration assemblages. As noted previously, laboratory studies have shown that the rate of gas release from rocks is enhanced at stress levels associated with microfracturing (HOLUB and BRADY, 1981;SOBOLEV eta/., 1984;KATOH eta/., 1985). Field investigations have reported coincident trends in regional stress changes and groundwater radon concentrations (WAKITA et a/., 1985), and in regional deformation changes and ground gas radon activities (THOMAS and KoYANAGI, 1986).…”
Section: Increased Reactive Surface Area Modelmentioning
confidence: 74%
See 1 more Smart Citation
“…Dissolution or alteration of fresh rock surfaces could significantly increase ion concentrations present in groundwater and would be especially noticeable in well-established aquifers where older rock surfaces have been passivated by the formation of equilibrium alteration assemblages. As noted previously, laboratory studies have shown that the rate of gas release from rocks is enhanced at stress levels associated with microfracturing (HOLUB and BRADY, 1981;SOBOLEV eta/., 1984;KATOH eta/., 1985). Field investigations have reported coincident trends in regional stress changes and groundwater radon concentrations (WAKITA et a/., 1985), and in regional deformation changes and ground gas radon activities (THOMAS and KoYANAGI, 1986).…”
Section: Increased Reactive Surface Area Modelmentioning
confidence: 74%
“…More porous rocks typically show greater volume losses; this decline is irreversible and is unlikely to account for repeated precursory anomalies or cyclic chemical changes in groundwater. Investigation of gas emanation from rocks shows that gas release declines at low to intermediate stresses, due to closure of the channels through which gases escape, and only at higher stresses does gas emanation increase appreciably (HoLUB, 1981;GIARDINI et a/., 1976;HoLUB and BRADY, 1981;HONDA et a/., 1982). The latter increase is accompanied by acoustic emissions associated with micro-fracturing and is believed to be the result of new pore volume formation associated with dilatency (SOBOLEV, 1984;.…”
Section: Pore Collapse Modelmentioning
confidence: 99%
“…Paradoxically, a few experimental studies in the history of Earth sciences have attempted to understand the relationships between radon emission rate and rock deformation. In their early and pioneer work, Holub and Brady (1981) performed uniaxial compression tests on granite samples to monitor changes in radon exhalation as a function of microfracturing. Tests were carried out by cycli-cally loading and unloading samples to increase rock damage.…”
Section: Introductionmentioning
confidence: 99%
“…Both mechanisms of radon transport -diffusion and advection -depend on both soil porosity and permeability, which at the same time vary as a function of the stress field (Holub & Brady, 1981). However, migration by diffusion is negligible, where a component of advective long-distance transport exists (Etiope & Martinelli, 2002).…”
Section: Anomalous Radon Concentration and Seismicitymentioning
confidence: 99%